Supporting Knowledge Workers’ Health and Well-Being in the Post-Lockdown Era - Tatiana Harkiolakis; Marcos Komodromos (Administrative Sciences, 2023)
The specific problem is that knowledge workers experience high levels of stress and burnout in their professional lives, a trend that increased due to the transition to remote work during the COVID-19 pandemic. This integrative literature review addresses this problem by answering the following research questions: (1) How can working in the post-lockdown era allow greater well-being, job satisfaction, and job security to abide?; and (2) How can mental capital be increased in the 21st century to ensure maximum health and positive well-being in the future employment arena and on a global scale? This review contributes to the literature on worker health and wellbeing, hybrid work arrangements, and knowledge workers’ professional experiences. The findings suggest that knowledge workers can only thrive in a hybrid work environment if organizations take an empathetic approach to manage these workers and give them sufficient autonomy and flexibility in determining their work conditions, in addition to ample opportunities for social interaction and professional advancement.